Safety of rapid intravenous of infusion acetaminophen - Needleman, Steven M. (Baylor Health Care System, 2013)
Intravenous acetaminophen, Ofirmev®, is approved for management of mild to moderate pain, management of moderate to severe pain with adjunctive opioids, and reduction of fever. The product is supplied as a 100 mL glass vial. As stated in the prescribing information, it is recommended to be infused over 15 minutes. This recommendation is related to the formulation propacetamol, the prodrug to acetaminophen, approved in Europe, which caused pain on infusion, and data from the clinical development of acetaminophen. The objective of this retrospective chart review study was to show the lack of side effects of rapidly infusing intravenous acetaminophen. Charts of American Society of Anesthesiology (ASA) Class I–III ambulatory surgical patients who received only acetaminophen in the preoperative setting were reviewed for any infusion-related side effects. Using standard binomial proportion analyses and employing SAS/JMP software, all vital signs were analyzed for statistically significant changes between pre- and postinfusion values. One hundred charts were reviewed. Only one patient had pain on infusion, which lasted 10 seconds. No reported side effects or erythema was seen at the injection site. No infusions had to be slowed or discontinued. The median infusion time was 3:41 minutes. Of the vital signs monitored, only the systolic (P < 0.0001) and diastolic (P < 0.0099) blood pressures had statistically significant changes from pre- to postinfusion; however, they were of no clinical relevance. Acetaminophen can be administered as a rapid infusion with no significant infusion-related side effects or complications.